STRENGTHENING ACCESS TO LEGAL SERVICES FOR THE ELDERLY IN ALL OF MACEDONIA VIA SMARTPHONES (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
This paper explores the role of smartphones in providing legal protection and support for older adults. Despite legal protections in place, older adults often face barriers to accessing legal services, due to lack of resources or mobility issues. This is particularly important for those in marginalized groups or people from rural areas. The easy availability of smartphones and the increase in technological literacy with the use of smartphones, older adults can access legal resources and support in an efficient and easy way, but unfortunately in our country it is still a "taboo" because the elderly in Macedonia they do not have enough experience and knowledge about the possibility of using legal protection and support. This paper discusses how smartphones, which are now readily available, can be used to help older adults exercise their rights, navigate the legal system, and report cases of abuse, harassment, or neglect. This paper discusses the potential challenges and limitations, as well as the lack of mobile applications specifically aimed at this age group of people. In conclusion, this paper shows the potential for smartphones to play a key role in being able to provide easy access to the service they need, while enabling legal protection and protection against misuse of personal data.
Keywords: legal protection, smartphones, support, older adults.